Promote the Application of the International Classification of Functioning， Disability and Health Rehabilitation Set in Musculoskeletal Rehabilitation - YAN Tiebin; XIE Hongwu (康复学报)
The Chinese version of the International Classification of Functioning, Disability and Health Rehabilitation Set (ICF-RS) was first published in China in 2017, and the clinical application of ICF-RS in rehabilitation in China is gradually increasing. The purpose of this study is to explore the feasibility and value of ICF-RS in the field of musculoskeletal rehabilitation in China, and to provide objective evidence for promoting the clinical application of ICF-RS in an all-round way. This study mainly introduces the development of International Classification of Diseases (ICD) and International Classification of Functioning, Disability and Health (ICF), the application status of ICF-RS in musculoskeletal rehabilitation and the measures to promote the application of ICF-RS in musculoskeletal rehabilitation. vThe application status of ICF-RS in musculoskeletal rehabilitation, including the functional classification of musculoskeletal rehabilitation, has not been paid enough attention; the feasibility analysis and challenges of ICF-RS in musculo-skeletal rehabilitation. In order to promote the application of ICF-RS in the field of musculoskeletal rehabilitation, it is necessary to establish the awareness of timely assessment of patients' function after orthopaedic surgery, clarify the functional orientation of orthopaedic rehabilitation after surgery, accept formal ICF-RS training, and improve the convenience of ICF-RS application based on APP.